Edukasi Penggunaan Media Baru dalam Penanggunalan Bencana Erupsi Gunung Merapi - Nur Amala Saputri (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2023)
This article discusses educational activities on the use of new media as an effort to deal with disaster events in Demen, Pakembinangun, Pakem, Sleman. This community service activity is carried out by providing training on the use of new media, such as: YouTube, WhatsApp, Twitter, and Google Maps. The methods used are reflections, lectures, simulations, discussions, and evaluations regarding digital media. The result is that the Demen people know that most of the people quite understand the types of communication media, both conventional media and new media that present disaster information. Only about 18 out of 20 participants thought that television and Facebook did not have a positive effect on disaster management. Meanwhile WhatsApp, Twitter and YouTube actually provide a lot of information that has a positive impact on them, mainly used to find the latest information updates, coordination and cooperation. This service activity also invites the public to use Google Map as a new form of collaboration in mapping evacuation routes and 3 gathering points when natural disasters such as the eruption of Mount Merapi occur. This effort was made to reduce the risk of social panic and reduce the possibility of traffic accidents when evacuating.